2020
DOI: 10.1080/14712598.2020.1815703
|View full text |Cite
|
Sign up to set email alerts
|

Regenerative application of stromal vascular fraction cells enhanced fat graft maintenance: clinical assessment in face rejuvenation

Abstract: Objectives:The aim of this study was to evaluate the safety and efficacy of the use of FG-SVFs in face rejuvenation for esthetic improvement. Methods: 33 female patients affected by face's soft-tissue defects with loss of volume, study group (SG), were treated with FG-SVFs, comparing results with a control group (CG) (n = 30) treated with fat graft not enhanced (FG). Clinical evaluation, a photographic assessment, magnetic resonance imaging (MRI), and ultrasound (US) were performed. Post-operative follow-up wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 53 publications
0
15
0
Order By: Relevance
“…Many previous studies and clinical trials have shown that stem cells therapy and related biotechnology hold a great promise in regenerative medicine applications [25][26][27][28]. BM-MSCs, adipose-derived mesenchymal stem cells (AD-MSCs), and stromal vascular fraction cells (SVFs) have the ability to promote wound healing and soft tissue defects when used alone [29][30][31] or in combination with platelet rich plasma (PRP) and fat graft [32][33][34].…”
Section: Discussionmentioning
confidence: 99%
“…Many previous studies and clinical trials have shown that stem cells therapy and related biotechnology hold a great promise in regenerative medicine applications [25][26][27][28]. BM-MSCs, adipose-derived mesenchymal stem cells (AD-MSCs), and stromal vascular fraction cells (SVFs) have the ability to promote wound healing and soft tissue defects when used alone [29][30][31] or in combination with platelet rich plasma (PRP) and fat graft [32][33][34].…”
Section: Discussionmentioning
confidence: 99%
“…However, almost the majority of these therapeutical methods have remained inconclusive and unsatisfactory and in fact no gold standard treatment has been provided for these lesions. Meanwhile, autologous fat grafting has been used as a comprehensive method for tissue repair in the recent decade, and in some studies [8][9][10], the effectiveness of this method in repairing the structure and formation of the skin and rejuvenation has been confirmed [11][12][13][14]. Fat tissue consists of two main components which are as follows: mature adipocyte cells and stromal vascular fraction (SVF) [15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, more work needs to be performed exploring the relationship between the pro-autophagy effect of BMSCs and other cell types in the context of wound healing, which may provide added insight into the influence of BMSCs on diabetic wound repair. For stem cell-based therapy, in addition to BMSCs as an alternative to repair and regenerate tissues, adipose-derived mesenchymal stem cells (AD-MSCs) can serve as a stem cell source for many tissue engineering applications, including wound healing [3,51], scars [52], skin photoaging [53,54], and COVID-19 treatment [55][56][57]. However, whether the paracrine mechanism of AD-MSCs is involved in regulating cell autophagy during wound repair is still unclear.…”
Section: Discussionmentioning
confidence: 99%